A literature review of intimate partner violence and its classifications - Ali, Parveen Azam; Dhingra, Katie; McGarry, Julie (Elsevier Masson, 2016)
Intimate partner violence is an important issue and attempts to distinguish typologies of intimate partner violence are necessary to understand the complexities of intimate partner violence, its various causes, correlates, and consequences. Over the last two decades, much research was aimed at classifying types of violence depending on the similarities and differences in patterns of violence. However, it is difficult to find a single account that provides a succinct and up-to-date overview of these classifications. As a result, considerable effort is required to identify and retrieve relevant papers to understand each typology or classification of intimate partner violence. This article provides a succinct and up-to-date integrative review of various classifications of intimate partner violence. Typologies by form of abuse, type of violence, type of perpetrator (men and women) are critically reviewed in the light of available literature and the strengths and limitations of each are described. Recommendations for further research are also provided.